Gypsy, Roma and Traveller Children in Child Welfare Services in England. (7th January 2022) - Allen, Dan; Hamnett, Victoria
Abstract: Over the last five decades, there has been a growing concern that Gypsy, Roma and Traveller children are overrepresented in child welfare services (CWS) in Europe. However, statistical data used to substantiate this concern often conflates ethnicity and nationality limiting our full understanding of the reported situation. This article provides a more comprehensive illustration of overrepresentation, advancing the quantitative study of this topic in England. Using a per capita division by population method, data obtained from the Department of Education were tested for disparity ratios across four key indicators. The analyses found that the recorded number of 'Gypsy/Roma' and 'Travellers of Irish Heritage' in CWS in England has been growing at a disproportionate rate since 2011–2012 to now demonstrate overrepresentation. The findings go beyond the concerns that have been raised to highlight a more specific need for remedial and restorative action. Implications are discussed for strategic responses to drive up data quality and further explore the details of the disparities that are found. Abstract : This article provides a comprehensive illustration of the overrepresentation of Gypsy, Roma and Traveller children in child welfare services (CWS) in England. Using a per capita division by population method, data obtained from the Department of Education (DfE) were tested for disparity ratios. Analyses found that the recorded Gypsy, Roma and Travellers children in CWS in England have been growing at a disproportionate rate since 2011. The findings presented go beyond the concerns that have been raised in the literature to highlight a more specific need for remedial and restorative action. The unique contribution of this study is the recommendation that specific approaches are now required to reduce the disparities that DfE data show.